PELATIHAN PEMBUATAN NAS SYSTEM BAGI SISWA TKJ SMK BINTANG NUSANTARA: PEMANFAATAN TEKNOLOGI SEBAGAI PENDORONG LITERASI DIGITAL - Ahmad; Abdul Rasyid Wicaksono; Altare Abdul Aziz Tjindarbumi; Usnul Padilah; Vera Yunita; Saffa Aldrian Saleh; Derifqi Restafi Maulana; Muhammad Idlal Hafizd; Rahmat Anugrah; Muhammad Fathir Syaifurrahman; Rayya Abdel Mawaddah (Abdi Jurnal Publikasi, 2024)
This Community Service Program (PKM) aims to enhance digital literacy among students in the Computer and Network Engineering (TKJ) department at SMK Bintang Nusantara through training on creating a Network-Attached Storage (NAS)-based storage system. The training includes an introduction to NAS technology, its implementation in the school network, and practical exercises in data management. The results showed a significant increase in students' understanding of NAS technology, with 80% of participants being able to independently comprehend the concepts and basic configuration of NAS and apply the system to support learning activities. Students' digital literacy also improved significantly, as evidenced by their ability to effectively manage data using the NAS system.